Medallion „Librarians in time and space”. Richard de Bury (1287 —1345) (Confluenţe Bibliologice, 2025)
Richard De Bury, a famous bibliophile of the Middle Ages, collected an impressive library of 1,500 books for future students at Oxford University, but his collection was unfortunately lost. He is famous for his work "Philobiblon", the first medieval encyclopedia of bibliophilia, written in Latin, where he spoke about the importance of books and the rules for reading and handling them.
Keywords: Bury Richard de (1287 - 1345)